2002
DOI: 10.1093/protein/15.3.243
|View full text |Cite
|
Sign up to set email alerts
|

A recombinant bacterial cell surface (S-layer)-major birch pollen allergen-fusion protein (rSbsC/Bet v1) maintains the ability to self-assemble into regularly structured monomolecular lattices and the functionality of the allergen

Abstract: The mature crystalline bacterial cell surface (S-layer) protein SbsC of Bacillus stearothermophilus ATCC 12980 comprises amino acids 31-1099 and assembles into an oblique lattice type. As the deletion of up to 179 C-terminal amino acids did not interfere with the self-assembly properties of SbsC, the sequence encoding the major birch pollen allergen (Bet v1) was fused to the sequence encoding the truncated form rSbsC(31-920). The S-layer fusion protein, termed rSbsC/Bet v1, maintained the ability to self-assem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 31 publications
2
39
0
Order By: Relevance
“…7) indicates that the C-terminal HA tag is exposed to the ambient environment, and Fourier transformation analysis revealed the formation of lattices with lattice spacing corresponding to that of native SslA of 13.2 nm (32). The results obtained by immunolabeling of selfassembly products are in good agreement with studies on various S-layer fusion proteins that exhibit C-terminally fused functional domains (e.g., streptavidin [2,25], birch pollen allergen [8,15,18], camel antibody [29], single amino acids [2], and enhanced green fluorescent protein [eGFP] [16]). Studies on structurefunction relationships revealed that the middle and, in some cases, the C-terminal parts of S-layer proteins are responsible for selfassembly into 2-dimensional protein arrays.…”
Section: Discussionsupporting
confidence: 82%
“…7) indicates that the C-terminal HA tag is exposed to the ambient environment, and Fourier transformation analysis revealed the formation of lattices with lattice spacing corresponding to that of native SslA of 13.2 nm (32). The results obtained by immunolabeling of selfassembly products are in good agreement with studies on various S-layer fusion proteins that exhibit C-terminally fused functional domains (e.g., streptavidin [2,25], birch pollen allergen [8,15,18], camel antibody [29], single amino acids [2], and enhanced green fluorescent protein [eGFP] [16]). Studies on structurefunction relationships revealed that the middle and, in some cases, the C-terminal parts of S-layer proteins are responsible for selfassembly into 2-dimensional protein arrays.…”
Section: Discussionsupporting
confidence: 82%
“…A chromosomal integration, utilizing the S-layer homologous motifs of the Bacillus anthracis S-layer proteins EA1 or Sap fused with levansucrase of B. subtilis, resulted in anchoring of the fusion protein to the bacterial cell surface (30). There are also reports on several non-Lactobacillus S-layer fusion proteins for which the protein production is plasmid derived either in a heterologous host (5,49) or in a null mutant lacking the wild-type S-layer protein gene (2). Our work is thus the first to describe the construction of a chromosomally encoded S-layer fusion protein, utilizing the entire S-layer protein gene.…”
Section: Discussionmentioning
confidence: 99%
“…The study was approved by the local medical ethics committee (Vienna, Austria). RSbsC-Bet v 1 and rSbsC were produced, as described (30). Endotoxin levels in rSbsC-Bet v 1 and rSbsC were below 0.4 EU/mg, as determined by Limulus amebocyte lysate assay (BioWhittaker).…”
Section: Patients Allergens and Reagentsmentioning
confidence: 99%
“…We have proposed to engineer allergy vaccines by genetic fusion of allergens with S-layer proteins: the major birch pollen allergen Bet v 1 was fused with the S-layer protein from the nonpathogenic bacteria Geobacillus stearothermophilus ATCC 12980 (30,31). The resulting allergen-S-layer fusion protein rSbsC-Bet v 1 induced IFN-␥ and IL-10 production in PBMC and Bet v 1-specific Th2 clones from birch pollen-allergic donors (31).…”
mentioning
confidence: 99%